Статистичний аналіз дорожньо-транспортних пригод у Тернопільській області та заходи щодо зниження аварійності - Ляшук О. Л.; Міронов, Д. В.; Лисенко, C. В.; Гупка, А. Б.; Бодоряк, Ю. Д.; Lyashuk, O.; Mironov, D.; Lysenko S.; Gypka, A.; Bodoriak. Yu. (ЦНТУ, 2024)
Проведено статистичний аналіз динаміки причин та наслідків дорожньо-транспортних пригод (ДТП) у Тернопільській області за останні п'ять років. Виявлено значне зростання кількості ДТП, що досягло 2547 випадків у 2023 році, з їх основними видами: зіткнення, наїзд на перешкоду, наїзд на транспортний засіб, що стоїть, та наїзд на пішохода. Виявлено основні причини ДТП для регіону і їх вплив на травматизм осіб, а саме: порушення правил маневрування, перевищення швидкості, недотримання дистанції, керування у нетверезому стані та порушення правил проїзду перехресть. Запропоновано стратегію зниження аварійності на автошляхах Тернопільської області, яка включає наступні заходи: впровадження штучних нерівностей, встановлення світлофорів із регульованими таймерами, додаткових дорожніх знаків, розмітки пішохідних переходів з підсвічуванням та використання камер спостереження для зниження аварійності. Розроблено заходи, які сприятимуть підвищенню безпеки дорожнього руху, зменшенню кількості ДТП та їх тяжкості, а також зниженню економічних втрат, пов'язаних з дорожньо-транспортними пригодами. Reducing Accident Rates The aim of this study is to analyze the dynamics, causes, and consequences of road traffic accidents (RTAs) in the Ternopil region over the past five years. This analysis seeks to identify the primary types of RTAs, determine the most frequent causes, and propose effective measures to reduce the number of accidents and their severity. By understanding these factors, we aim to enhance road safety and minimize the socioeconomic impacts associated with RTAs in this region. In this study, a comprehensive statistical analysis of RTAs in the Ternopil region was conducted. This analysis revealed a significant increase in the number of accidents, which reached 2547 cases in 2023, an 11% rise compared to 2022. The primary types of accidents identified include collisions (50%), hitting obstacles (19%), hitting stationary vehicles (16%), and pedestrian accidents (8%). The study found that the highest mortality rates occur in pedestrian accidents (34%) and vehicle collisions (33%). Key causes of RTAs were identified as violations of maneuvering rules (40%), speeding (23%), failure to maintain a safe distance (10%), driving under the influence of alcohol (7%), and violations at intersections (5%). Based on these findings, several recommendations were made to enhance road safety. These include the implementation of artificial road bumps, installation of traffic lights with adjustable timers, additional road signs, high-visibility and illuminated pedestrian crossings, and the use of surveillance cameras to monitor compliance with traffic rules and identify violators. Moreover, the study emphasizes the importance of developing and implementing methodologies for predicting accident rates using statistical methods and conflict zone analysis, as well as calculating accidentrelated economic and environmental losses to evaluate the effectiveness of proposed measures.
Statistical Analysis of Road Traffic Accidents in Ternopil Region and Measures for Reducing Accident Rates
Keywords: дорожньо-транспортні пригоди; безпека дорожнього руху; причини ДТП; зниження аварійності; травматизм на дорогах; порушення ПДР; прогнозування ДТП; road traffic accidents (RTA); road safety; causes of RTAs; accident reduction; traffic injuries; traffic violations; accident prediction